Marine Early Triassic Actinopterygii from Elko County (Nevada, USA): implications for the Smithian equatorial vertebrate eclipse. (19th July 2017) - Romano, Carlo; Jenks, James F.; Jattiot, Romain; Scheyer, Torsten M.; Bylund, Kevin G.; Bucher, Hugo
Abstract: The Early Triassic vertebrate record from low paleolatitudes is spotty, which led to the notion of an 'equatorial vertebrate eclipse' during the Smithian. Here we present articulated ray-finned fishes (Actinopterygii), collected from the marine Lower Triassic Thaynes Group at three new localities in Elko County (Nevada, USA), which were deposited within the equatorial zone. From the Smithian of the Winecup Ranch, we describe two partial skulls of the predatory actinopterygian Birgeria (Birgeriidae), attributed to B . americana new species and Birgeria sp. Birgeria americana n. sp. is distinguished from other species by a less reduced operculogular series. With an estimated total length of 1.72–1.85m, it is among the largest birgeriids. We confirm that Birgeria encompasses species with either two or three rows of teeth on the maxilla and dentary, and suggest that species with three well-developed rows are restricted to the Early Triassic. From the latest Smithian of Palomino Ridge, we present a three-dimensional, partial skull of the longirostrine predator Saurichthys (Saurichthyidae). This and other occurrences indicate that saurichthyids were common in the western USA basin. From the early late Spathian of Crittenden Springs, we describe a posterior body portion (Actinopterygii indet.). This find is important given the paucity of Spathian osteichthyan sites. We provide a summary of Early Triassic vertebrate occurrences in the United States, concluding that vertebrate fossils remain largely unstudied. The presence of predatory vertebrates in subequatorial latitudes during the Smithian confirms that Early Triassic trophic chains were not shortened and contradicts the 'equatorial vertebrate eclipse'.